Kekerasan Gender pada Naskah Drama Rajam (Pelempar Batu Pertama) Karya Idham Nurcahyo: Kajian Feminisme - Ali, Ayu Hidayanti; Kadir, Herson; Sadapu, Nurain; Justevani, Sri; Dunggio, Sri Juliana Mul’afaida (Jurnal Bahasa, Sastra, dan Budaya, 2024)
Violence against women remains a serious issue in society, both in the domestic and public spheres, and is often represented in literary works, including drama scripts. This study analyzes the drama script "Rajam (Pelempar Batu Pertama)" by Idham Ardi Nurcahyo, which depicts the bitter reality of women in a patriarchal society. Through a feminist approach, this study identifies various forms of gender violence experienced by female characters, including sexual violence in marriage, victim-blaming, and symbolic violence. In addition, the role of society in perpetuating gender violence is also explored, especially through mechanisms of social judgment, the spread of irresponsible information (cyberbullying), and gender inequality in responding to cases of violence. The results of the analysis show that society contributes to strengthening patriarchal norms that are detrimental to women. Thus, this script not only serves as a critique of the practice of gender violence, but also as an invitation to reflect on and change discriminatory mindsets and behaviors in society. This research is expected to provide deeper insight into the importance of creating a more just and safe environment for women.